Modulation of Fibroblast Phenotype by Colorectal Cancer Cell-Secreted Factors Is Mostly Independent of Oncogenic KRAS - Patrícia Dias Carvalho; Susana Mendonça; Flávia Martins; Maria José Oliveira; Sérgia Velho (Cells, 2022)
KRAS mutations have been shown to extend their oncogenic effects beyond the cancer cell, influencing the tumor microenvironment. Herein, we studied the impact of mutant KRAS on the modulation of the pro-tumorigenic properties of cancer-associated fibroblasts (CAFs), including α-SMA expression, TGFβ1 and HGF production, extracellular matrix components and metalloproteinases expression as well as collagen contraction and migration capacities. To do so, CCD-18Co normal-like colon fibroblasts were challenged with conditioned media from control and KRAS silenced colorectal cancer (CRC) cells. Our results showed that the mutant KRAS CRC cell-secreted factors were capable of turning normal-like fibroblasts into CAF-like by modulating the α-SMA expression, TGFβ1 and HGF production and migration capacity. Oncogenic KRAS played a secondary role as its silencing did not completely impair the capacity of CRC cells to modulate most of the fibroblast properties analyzed. In summary, our work suggests that mutant KRAS does not play a major role in controlling the CRC cell-secreted factors that modulate the behavior of fibroblasts. The fact that CRC cells retain the capacity to modulate the pro-tumorigenic features of fibroblasts independently of KRAS silencing is likely to negatively impact their response to KRAS inhibitors, thus standing as a putative mechanism of resistance to KRAS inhibition with potential therapeutical relevance.